The Design of the Four-port MIMO Antenna at 28 GHz with Isolation Enrichment for 5G Communication - Ravi Kumar Goyal; Uma Shankar Modani (Research and Developments in Engineering Research Vol. 2, 2023)
This study concentrates on the miniaturization of MIMO antenna with improved isolation. MIMO micro strip patch antenna with four radiating elements is designed3 at . The designed antenna has a very low isolation loss between radiating antenna elements. The CST Microwave simulator is used to simulate the MIMO antenna. This paper also displays the measurement results. In order to evaluate the performance of the antenna, simulation and measurement results are both examined. At a center frequency of 28 GHz, the characteristics of the MIMO patch antenna, such as return loss, VSWR, gain, beam-width, and radiation pattern, are examined. The isolation loss between the MIMO antenna elements is investigated experimentally with inter-element spacing of . The envelope correlation coefficients among the elements, the mean effective gains, the efficiencies are also discussed. The designed antenna is planner, compact and thin so it is applicable for 5G handset.